Association of exposure to organophosphate esters with increased blood pressure in children and adolescents. (15th February 2022) - Hu, Liqin; Yu, Meng; Li, Yaping; Liu, Ling; Li, Xiang; Song, Lulu; Wang, Youjie; Mei, Surong
Abstract: Organophosphate esters (OPEs) are widely added to various industrial and consumer products, and are mainly used as flame retardants and plasticizers. Existing epidemiological studies suggest that OPE exposure may be linked to increased blood pressure (BP) and hypertension risk in adults. However, it remains unclear whether OPE exposure is associated with increased BP in children and adolescents. Here, we investigated the associations between OPE exposure and BP levels in 6–18-year-old children and adolescents from a cross-sectional study in Liuzhou, China. OPE metabolites were determined in spot urine samples (n = 1194) collected between April and May 2018. Three measurements of systolic and diastolic BP for each participant were averaged as study outcomes. Associations of OPE exposure with age-, sex- and height-standardized BP were assessed using linear regression models. We found that each natural log unit increment of bis(1, 3-dichloro-2-propyl) phosphate (BDCIPP) was associated with a 0.06 standard deviation unit (95% confidant interval (CI): 0.01, 0.11) increase in systolic BP z-score. When conducting stratified analysis based on sex, age, and BMI category, BDCIPP was shown to be positively associated with systolic/diastolic BP z-score in females, but not in males. The associations between bis(2-butoxyethyl) phosphate (BBOEP) and systolic/diastolic BP z-score were pronounced in adolescents, but not in children. Moreover, a significant positive association between 1-hydroxy-2-propyl bis(1-chloro-2-propyl) phosphate (BCIPHIPP) and diastolic BP z-score was observed in obese subjects. The present study provides the first evidence that OPE exposure was related to increased BP in children and adolescents. Given the scarcity of high-quality evidence supporting these results, the health effects of OPEs are warrant investigation in well-designed prospective studies. Graphical abstract: Image 1 Highlights: The first study to explore the association of OPE exposure with blood pressure (BP) in children and adolescents. A positive linear association was observed between urinary BDCIPP and systolic BP z-score. OPEs-BP z-score associations were more evident in females, adolescents, or obese subjects.